2020
DOI: 10.1101/2020.06.18.158329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphism and selection pressure of SARS-CoV-2 vaccine and diagnostic antigens: implications for immune evasion and serologic diagnostic performance

Abstract: The ongoing SARS-CoV-2 pandemic has triggered multiple efforts for serological tests and vaccine development. Most of these tests and vaccines are based on the Spike glycoprotein (S) or the Nucleocapsid (N) viral protein. Conservation of these antigens among viral strains is critical to ensure optimum diagnostic test performance and broad protective efficacy, respectively. We assessed N and S antigen diversity from 17,853 SARS-CoV-2 genome sequences and evaluated selection pressure. Up to 6-7 incipient phyloge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The V483A mutation site does not form direct contact with the ACE2 receptor, but it is on the same face of the RBD that includes the binding interface with the ACE2 [ 18 ]. Along with V483A, other mutations were reported at the 483rd position of the RBD where Val is getting substituted to other amino acids such as phenylalanine (Phe), isoleucine (Ile), proline (Pro), aspartic acid (Asp), arginine (Arg) and lysine (Lys) in very low occurrence rate [ 19 , 20 ].…”
Section: Structure Analysis Of Mutant Proteinmentioning
confidence: 99%
“…The V483A mutation site does not form direct contact with the ACE2 receptor, but it is on the same face of the RBD that includes the binding interface with the ACE2 [ 18 ]. Along with V483A, other mutations were reported at the 483rd position of the RBD where Val is getting substituted to other amino acids such as phenylalanine (Phe), isoleucine (Ile), proline (Pro), aspartic acid (Asp), arginine (Arg) and lysine (Lys) in very low occurrence rate [ 19 , 20 ].…”
Section: Structure Analysis Of Mutant Proteinmentioning
confidence: 99%
“…The N501Y mutation of the spike protein (S) has also been implicated in the rapid spread of two new strains in the United Kingdom and South Africa (4)(5)(6). Of additional concern, it is possible that some mutations may enable immune evasion and reduced vaccine efficacy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Out of these mutations, D614 G mutation (causing aspartate to glycine at 614 in S protein ) is reported to be the most prevalent mutations in Europe, Oceania, South America, Africa, Middle East, and India ( Gong et al, 2020 ; Raghav et al, 2020 ; Zhang et al, 2020 ). Several laboratory experiment-based investigations have reported that the level of angiotensin-converting enzyme 2 ( ACE2) expression was distinctly higher by the retroviruses pseudo-typed with G614 compared with that of D614 in cell culture experiments ( Dumonteil and Herrera, 2020 ; Zhang et al, 2020 ). Another reported mutation of ORF1ab is P4715 L linked with D614 G, which is linked with higher fatality rates in 28 countries and 17 states of the United States ( Mercatelli and Giorgi, 2020 ; Toyoshima et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%